The role of socio-economic characteristics in predicting peak period appliance use - William Brazil; Jason Harold; John A. Curtis (The Economic and Social Research Institute (ESRI), 2019)
Household appliances represent significant load demand within the domestic electricity market, and therefore present considerable challenges for grid managers, specifically during peak demand periods. This paper presents the results of a statistically representative study of Irish households, undertaken specifically to assess peak period domestic appliance use, with respect to time of use and the socio-economic characteristics of the users. Specific attention is devoted to both an analysis of appliance use patterns, and to the likelihood of individuals using such appliances during the evening peak period, with respect to socio-economic characteristics. Results highlight the presence of potentially deferrable load associated with domestic appliances within the evening peak. Findings from both logit and zero-inflated negative binomial models provide insights into differences in appliance use patterns with regard to employment status, household size, the number of individuals present in the home during the day, and respondents' income. These results highlight the possibility of either targeted marketing campaigns to encourage appliance deferral to periods of lesser demand, or direct load control to reduce peak period appliance demand. In particular, both engagement in full time employment and number of household members present in the home during the day, are found to be significant predictors of whether or not a given household is a peak period appliance user. This suggests that there is scope for automated or remote appliance control to reduce peak period load without adversely impacting consumers. In contrast, household size and income emerge as predictors of the number of appliance use events that occur during the evening peak period.
Keywords: D1; 330; Domestic Appliances; Household Characteristics; Direct Load Control